1985
DOI: 10.1073/pnas.82.6.1736
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Na+/H+ antiport is an early event in hypertrophy of renal proximal tubular cells.

Abstract: Renal hypertrophy in vivo is achieved by an increase in protein content per cell and an increase in cell size with minimal hyperplasia. Hypertrophied renal tubular cells remain quiescent and demonstrate an increase in transcellular transport rates. This situation was simulated in vitro by exposing a confluent, quiescent primary culture of rabbit renal proximal tubular cells to either insulin, prostaglandin E1, or hypertonic NaCl for 24 or 48 hr. Protein per cell increased by 20-30% with little or no increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 68 publications
(33 reference statements)
2
53
0
Order By: Relevance
“…For example, glucocorticoids (14), thyroid hormones (15) and metabolic acidosis (16) increased Na/H exchange in brush border membrane vesicles isolated from rats. Insulin and prostaglandin E1 stimulated Na/H exchange in cultured proximal tubular cells (8) . Gesek and coworkers demon Takahashi et …”
Section: Effects Of Insulin On Phi Of Pstmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, glucocorticoids (14), thyroid hormones (15) and metabolic acidosis (16) increased Na/H exchange in brush border membrane vesicles isolated from rats. Insulin and prostaglandin E1 stimulated Na/H exchange in cultured proximal tubular cells (8) . Gesek and coworkers demon Takahashi et …”
Section: Effects Of Insulin On Phi Of Pstmentioning
confidence: 90%
“…However, insulin effect on Na/H exchange is controversial. Fine and colleagues demonstrated that insulin increases Na/H exchange in primary cultures of rabbit proximal tubular cells (8). In contrast, Mellas and co-workers reported that insulin had no stimulatory effect on Na/H exchange in canine proximal tubular cells (9).…”
mentioning
confidence: 99%
“…After achieving confluence (8-12 days), cells were rendered quiescent by removal of insulin and hydrocortisone for 48 hr prior to and during preincubation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Fetal bovine serum was added to 3% (vol/vol) to the culture medium for the first 3 days to allow better cell attachment. After achieving confluence (8-12 days), cells were rendered quiescent by removal of insulin and hydrocortisone for 48 hr prior to and during preincubation (10).…”
mentioning
confidence: 99%
“…The recent advance in micropuncture techniques of ion-selective microelectrodes has made it possible to measure the intra-and extra-cellular ion activities, examining the movement of Na + and H + across the brush border membrane (BORON and BoULPAEP, 1983;SAsAKI et al, 1985). In the previous in vitro studies, it was shown that Na + /H + exchange was inhibited by cyclic AMP (cAMP) in the brush border vesicle from proximal tubular cells of rat kidney (KAHN et al, 1985), or stimulated by insulin in primary cultures of proximal tubular cells (FINE et al, 1985). Recently in our laboratory, we found a specific binding of insulin to the bullfrog kidney mass and homogenate (unpublished observation).…”
mentioning
confidence: 99%